Year‐Round Nitrous Oxide Emissions as Affected by Timing and Method of Dairy Manure Application to Corn. Issue 1 (2nd February 2017) - Cambareri, Gustavo; Drury, Craig; Lauzon, John; Salas, William; Wagner-Riddle, Claudia
Abstract : Core Ideas: The year × timing interaction affects cumulative N2 O emissions. Injection of manure produces the highest cumulative N2 O emissions. Injection of manure produces the highest corn yields. Manure application to agricultural soils enhances N2 O emissions, but these emissions could be reduced by using improved application methods at the right time. We conducted a 3‐yr study on corn ( Zea mays L.) grown in Elora, ON, Canada, to test the effects of timing and method of liquid dairy manure application on year‐round N2 O emissions. A randomized complete block design was set up every year evaluating two application times (fall vs. spring) and three methods of manure application (surface broadcasting, incorporation, and injection). Lower cumulative N2 O emissions for fall than spring application (mean ± standard error = 1.2 ± 0.3 vs. 2.9 ± 0.3 kg N2 O‐N ha −1 ) were found during the driest year (2012), whereas no differences in emissions occurred between application timing in near‐normal precipitation years (2013 and 2014). Nitrous oxide emissions were not affected by the timing × method of application interaction. Injected manure resulted in cumulative N2 O emissions not different than surface broadcast manure (3.6 ± 0.5 vs. 3.0 ± 0.5 kg N2 O‐N ha −1 ) but significantly higher than incorporated manure (2.2 ± 0.3 kg N2 O‐N ha −1 ). Injection resulted in greater corn yields than the other two methods. Our results suggest that (i) method of application affects N2 O emissions independently of timing; (ii) including N2 O emissions for the non‐growing season avoided biased estimates for the fall application timing since 20 to 60% of total emissions occurred during this period; and (iii) incorporating manure is the best practice to mitigate N2 O emissions, although if N rates are optimized, injection could potentially produce yields with low N2 O intensity.